2021
DOI: 10.3390/app11020652
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and Flow Aspects of Synthetic Jet Actuators with Chevron Orifices

Abstract: The use of a chevron nozzle/orifice is one of the methods of heat transfer enhancement and noise reduction. In the case of synthetic jets, the number of papers on this topic is small. Therefore, a synthetic jet actuator with three different chevron orifices and one circular orifice is investigated. The aim of this study is to find the impact of orifice shape on centerline velocity (measured with a hot-wire anemometer) and determine if the chevron orifice reduces the generated noise. The sound pressure level wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…The loudspeaker STH M. 18.200.8.MCX was used. The same actuator but with other orifices was used in [29].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The loudspeaker STH M. 18.200.8.MCX was used. The same actuator but with other orifices was used in [29].…”
Section: Methodsmentioning
confidence: 99%
“…It made that the vortex ring is not circular but more complex, but dissipate faster than vortices in the case of the circular nozzle. Smyk and Markowicz [29] showed that the time-average centerline velocity is the same for chevron and circular SJ in a distance x/d = 6, where x is an axial distance from the orifice and d is an orifice diameter. During, the centerline momentum velocity was the same, regardless of the type of orifice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many studies and research projects treating the jet noise reduction [5,6], but the simplest technique is to manufacture chevrons on the nozzle without having high loss of the propulsion force [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%